2022
DOI: 10.3390/pathogens12010055
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Differences of Meconium Microbiomes of Preterm and Term Infants, and Infants That Developed Necrotizing Enterocolitis or Feeding Intolerance

Abstract: The primary aim of this study was to investigate the compositional differences of the first passed meconium microbiome in preterm and term infants, and the secondary aim was to compare the meconium microbiomes of preterm and term infants that later developed necrotizing enterocolitis (NEC)/Feeding intolerance (FI) compared to those that did not develop NEC/FI. During the study period, a total of 108 preterm and term newborns' first passed meconium occurring within 72 hours of birth were collected and microbiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The R package decontam (version 1.8.0) was used to filter out environmental contaminants from each sample type [22]. The detailed sampling, preprocessing, and analysis methods used for the meconium samples have been published elsewhere [13].…”
Section: Fecal Microbiome Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The R package decontam (version 1.8.0) was used to filter out environmental contaminants from each sample type [22]. The detailed sampling, preprocessing, and analysis methods used for the meconium samples have been published elsewhere [13].…”
Section: Fecal Microbiome Analysis Methodsmentioning
confidence: 99%
“…However, recently, it was reported that the mode of delivery had a transitional and small effect on neonates' gut microbiota and that gestational age (GA) seems to be the main driver of neonates' gut microbiota [12]. Because GA at birth represents the time of first microbial exposure, the microbiota composition of preterm infants is significantly different from that of full-term (FT) infants [13,14]. Very preterm (VP) infants present three main gut microbiota phyla: Firmicutes, Bacteroidetes, and Proteobacteria, which account for most community dynamics.…”
Section: Introductionmentioning
confidence: 99%